(3aVGFd TgQ QLHs - (3Gdbej, GHf HGnHnhrjg, CHh LYaQ, GdUOhb, eMeO Hf Ydj Hf GdMSjf Hf ehSi, J (B381 (3gs ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3CNHQfG CHh LYaQ eMeO Hf Ydj Hf GdMSjf Hf ehSi Hf HGHhjg QVj Gddg Yfg bGd MOKfG eMeO Hf EHQGgje Hf ESMGb GdWGdbGfj bGd MOKfG CMeO Hf eMeO Gdchaj GdgeOjGfj (B...s
(3BNQgG (B:s
... (3EdG Gf jSGdg aj eCKe Ch bWjYI QMe hef UGe TgQ QLH cdg NQL ef PfhHg cjhe hdOJg Geg hGYJb ef GdfGQ hCONd GdLfI eY GdeUWajf GdCNjGQ (B. (3Jes
(3efbhdI Yf fSNI (B: (3GdTjN TjQ eMeO Hf UaQ Ydj GdgePGfj GdLhQbGfj Yf fSNI Yf fSNI Yf fSNI HNW GdeUfas
(3JHUQI GdYfhGf (B:s
(3Ydi WQI GdQSGdI HNW GdeUfa (B: (3PcQ GdeUfa gPG GdcJGH aj BNQ HGH KhGH Uhe QLH aj cJGHg eG dG jMVQg Gdabjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 \274s
(3GdPQjYI (B16 - 178 ( 1012 )s
Keywords: (3GdMOjK hGdeUWdMs